Use of eHealth to Facilitate Diet and Exercise Tracking and Discussions Between Cancer Survivors and Clinicians. (29th May 2020) - Lin, Annie; Tello, Leslie; Linville, Twila; Spring, Bonnie
Abstract: Objectives: Cancer-specific diet and exercise recommendations are not often discussed during oncology visits due to limited time and resources. eHealth [i.e., apps, activity trackers, electronic medical records (EMR)] could facilitate patient-clinician communication about health behaviors, but it is unknown how cancer survivors use eHealth and how engaged they are with digital technologies. We investigated cancer survivors' eHealth practices and whether their engagement differs from those without a cancer history. Methods: Cycle 1 and 2 data from the National Cancer Institute Health Information National Trends Survey 5 were used for this study. Of the 6751 adults included in our analysis, 1097 had a cancer history; the remainder served as the comparison group. We examined participants' engagement with tablets and/or smartphone apps and the EMR. Adjusted polytomous logistic regression models were performed to estimate associations between cancer history and eHealth engagement. Descriptive results were weighted, and the jackknife replication method was used to account for the complex sampling design. Significance threshold was set at p < 0.05. Results: Cancer survivors had a mean age of 64.2 ± 0.8 years and a mean BMI of 28.2 ± 0.3 kg/m 2 . Approximately one-third of cancer survivors used an app to track progress toward health goals and a tablet to facilitate health discussions with a clinician; 20% of cancer survivors shared data from a tracker and/or smartphone with a clinician. Further, 43% of cancer survivors accessed their EMR ≥ 1 time in the past year and 22% downloaded EMR data to their own devices. Cancer survivors were more likely to access the EMR ≥ 10 times in the past year than the comparison group, after adjusting for age, race, gender, education, income, and BMI [OR = 1.93 (95% CI: 1.12, 3.34), p = 0.02]. No other differences in eHealth engagement were observed between those with and without a cancer history. Conclusions: Our results demonstrate that cancer survivors are beginning to engage with eHealth to manage their health and communicate with clinicians. Both health apps and the EMR appear to be underutilized yet promising ways to deliver health recommendations for cancer survivors. Future research should investigate patterns of eHealth use among different subgroups of cancer survivors. Funding Sources: The first author is supported by the National Cancer Institute.